1989
DOI: 10.1152/ajpgi.1989.257.6.g898
|View full text |Cite
|
Sign up to set email alerts
|

Impaired acetylcholine release from the myenteric plexus of Trichinella-infected rats

Abstract: We examined the release of acetylcholine (ACh) from jejunal longitudinal muscle-myenteric plexus preparations in noninfected control rats and in rats infected 6, 23, or 40 days previously with Trichinella spiralis. ACh release was assessed by preincubating the tissue with [3H]choline and measuring the evoked release of tritium. The uptake of 3H was significantly less in tissue from T. spiralis-infected rats compared with control. In tissues from either infected or control animals, electrical field stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
70
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 0 publications
9
70
0
Order By: Relevance
“…Furthermore, there were increased numbers of ChAT IR inflammatory cells in the mucosa and submucosa, many appearing to be eosinophils, which are found in significant numbers in the jejuna of nematode-infected rats (Nawa and Hirashima 1984). In light of these inflammatory changes, it is interesting that altered cholinergic metabolism in animal models of intestinal inflammation has been reported (Collins et al 1989). Because ChAT can catalyze both the degradation and synthesis of acetylcholine (Molenaar 1990), our data suggest that information obtained from tissue homogenates should be interpreted with caution.…”
Section: Figurementioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, there were increased numbers of ChAT IR inflammatory cells in the mucosa and submucosa, many appearing to be eosinophils, which are found in significant numbers in the jejuna of nematode-infected rats (Nawa and Hirashima 1984). In light of these inflammatory changes, it is interesting that altered cholinergic metabolism in animal models of intestinal inflammation has been reported (Collins et al 1989). Because ChAT can catalyze both the degradation and synthesis of acetylcholine (Molenaar 1990), our data suggest that information obtained from tissue homogenates should be interpreted with caution.…”
Section: Figurementioning
confidence: 84%
“…However, recent studies employing immunohistochemical methods have shown alterations in tissue levels or nerve staining patterns for specific neuropeptides in gastrointestinal disorders, such as in-flammatory bowel diseases (Sjolund et al 1983;Goldin et al 1989;Strobach et al 1990;Kubota et al 1992). Furthermore, studies in experimental animals suggest that neurotransmitter metabolism might be affected by the inflammatory process (Collins et al 1989Swain et al 1991Swain et al ,1992. It has even been suggested that cholinergic nerves may participate in the interrelationship between the autonomic nervous system and the immune system (Rinner and Schauenstein 1993).…”
mentioning
confidence: 99%
“…In addition, the decrease in muscarinic response may contribute to the suppression of phasic contractions during colitis. It is possible that during colitis ACh release by myenteric plexus may be decreased as noted in ileitis (12), however exogenous arterial muscarine infusion did not stimulate increased activity during colitis. Thus, these findings suggest the myogenic response is dependent on the muscarinic receptor and postreceptor activation during normal and colitis states.…”
Section: Colitis Inhibits Colonic Circular Musclementioning
confidence: 88%
“…The inhibitory effect of colonic inflammation on spontaneous phasic contractions has been observed in earlier studies (9 -11). In vitro, at the myenteric plexus level at least in rats, excitatory neuronal function may be inhibited, resulting in a decrease in the release of ACh (12), whereas at the circular muscle cell, there may be a decrease in the density or affinity of muscarinic receptors (13).…”
mentioning
confidence: 99%
“…Although lines of evidence have indicated that activation of enteric neurons is an important component of an intricate defence process aimed at eliminating T. spiralis larvae from the GI tract lumen (Collins et al, 1989;Palmer et al, 1998), the neurochemical mechanisms underlying this action remain to be clarified. It has been discovered that during the first six days of T. spiralis infection cholinergic innervation of the rat jejunum undergoes rapid alterations (Collins et al, 1989;Davis et al, 1998) whereas the levels of noradrenaline released by extrinsic nerves projecting to the jejunum fall (Swain et al, 1991). Moreover, in rats intrarectally infected with T. spiralis larvae (animal model of ulcerative colitis) several changes in neurochemical properties of enteric neurons were observed at 6 and 14 days post infection (PI; Auli et al, 2008).…”
mentioning
confidence: 99%